2020
DOI: 10.1021/acs.molpharmaceut.0c00180
|View full text |Cite
|
Sign up to set email alerts
|

In Search of Advanced Tumor Diagnostics and Treatment: Achievements and Perspectives of Carbonic Anhydrase IX Targeted Delivery

Abstract: The research of how cells sense and adapt the oxygen deficiency has been recognized as worth winning a Nobel Prize in 2019. Understanding hypoxiadriven molecular machinery paved a path for novel strategies in fighting hypoxia-related diseases including cancer. The oxygen depletion inside the tumor provokes HIF-1 dependent gene and protein expression which helps the tumor to survive. For this reason, tumor related molecules are in the spotlight for scientists developing anticancer agents. One such target is car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 109 publications
0
8
0
Order By: Relevance
“…Condensation of compound 6 with triethyl orthoformate provided the Cy3 derivative, 3-dodecyl-2-((E)-3-((E)-3-dodecyl-3methylindolin-2-ylidene)prop-1-en-1-yl)-3-methyl-3H-indole (7). Subsequent ring-closing reaction via nucleophilic substitution between compound 7 and 3,5-bis(bromomethyl)-4-nitrobenzoic acid (11) resulted in the 12-membered macrocyclic compound (5 2 Z,7E)-3 5 -carboxy-1 3,53 -didodecyl-1 3,53 -dimethyl-3 2nitro-1 3 H-1,5(1,2)-diindol-1-iuma-3(1,3)-benzenacyclooctaphan-7-en-1 1 -ium (Cy3L).…”
Section: Papermentioning
confidence: 99%
See 4 more Smart Citations
“…Condensation of compound 6 with triethyl orthoformate provided the Cy3 derivative, 3-dodecyl-2-((E)-3-((E)-3-dodecyl-3methylindolin-2-ylidene)prop-1-en-1-yl)-3-methyl-3H-indole (7). Subsequent ring-closing reaction via nucleophilic substitution between compound 7 and 3,5-bis(bromomethyl)-4-nitrobenzoic acid (11) resulted in the 12-membered macrocyclic compound (5 2 Z,7E)-3 5 -carboxy-1 3,53 -didodecyl-1 3,53 -dimethyl-3 2nitro-1 3 H-1,5(1,2)-diindol-1-iuma-3(1,3)-benzenacyclooctaphan-7-en-1 1 -ium (Cy3L).…”
Section: Papermentioning
confidence: 99%
“…CA-IX is known to be overexpressed in MCF-7 and MDA-MB-468 cell lines. 7,24 Whereas, HEK293 is a CA-IX negative cell line. The MTT analysis revealed that MCF-7 cells were viable in the presence of control amphiphile Cy3L (without or with NIR-light treatment).…”
Section: Cellular Activities Of the Amphiphilementioning
confidence: 99%
See 3 more Smart Citations